Late Triassic traversodont cynodonts from Nova Scotia and southern Africa - Hopson, James A. (Bernard Price Institute for Palaeontological Research, 1984)
The first gomphodont cynodont from North America is described from the Upper Triassic Wolfville Formation, Fundy Group, Newark Supergroup, of Burntcoat, Minas Basin, Nova Scotia, Canada. Known material consists of a large mandible, edentulous but for two incisors, a probably associated canine, and two small dentaries; an isolated multicusped tooth may belong to this species. This gomphodont closely resembles the large traversodont Scalenodontoides macrodontes from the lower Elliot Formation (= Red Beds) of Lesotho; it is provisionally placed in this genus but is a distinct species, ?Scaleno- dontoides plemmyridon sp. nov. It differs from S. macrodontes primarily in its more massive symphyseal region and much larger mental foramen from which a prominent groove extends posterodorsally. The large, posteriorly-located mental foramen is believed to be a well-developed oral vestibule and cheek. The isolated tooth, provisionally interpreted as a traversodont lower postcanine, is anteroposteriorly compressed, with a high anterior blade formed by three transversely-aligned cusps and a short heel; it does not resemble postcanines of S. macrodontes and so reference to ?S. plemmyridon is questionable. Scalenodontoides is the sister genus of Exaeretodon from the Late Triassic of Argentina, Brazil, and India; they are allied on the basis of: upper incisors reduced from 4 to 3, all incisors greatly enlarged, and internarial bar incomplete. These resemblances to tritylodontids are convergent. Scalenodontoides and Exaeretodon share with Gomphodontosuchus the enlargement of the anterolabial cusp of the lower postcanines and posterior inclination of the anterolingual cusp. The Wolfville and basal Elliot faunas are considered to be Late Carnian or Carno-Norian in age. Faunas containing Exaeretodon are older Carnian, though the Santa Maria Formation of Brazil may be Late Ladinian.
Keywords: gomphodont; Wolfville Formation; Fundy Group; Newark Supergroup; Minas Basin; Canada; Scalenodontoides; Lesotho; Late Carnian; Norian; Burntcoat